Konstrukcijski materiali: Učbenik - Anžel, Ivan; Brunčko, Mihael (University of Maribor Press, 2022)
Engineering Materials: Textbook.The textbook is intended as a basic literature, for students of the 1st level of the study programs Mechanical Engineering, Industrial Engineering and Mechatronics. The textbook consists of three independent chapters, which as a whole bring knowledge in the field of materials and technologies and are needed in the development, research and use of materials in mechanical engineering, electrical engineering, automation, power industry ... The first chapter deals with typical groups of engineering materials and their structure. The basic concepts and facts about materials needed to understand their properties are described. The second chapter discusses the key properties of engineering materials that enable the successful selection of materials for a particular application. The third chapter contains selected examples of engineering materials. It describes special steels for use in mechanical engineering, light alloys, engineering ceramics, ceramic glasses and polymer materials.